2022
DOI: 10.2147/rmhp.s374385
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Acceptance of COVID-19 Vaccines in Citizens of Northern Peru: Cross-Sectional Study

Abstract: Purpose The presence of the COVID-19 coronavirus in Peru, and especially in northern Peru, was very fast and caused many deaths. As a result, vaccination proved to be the most immediate option to control it. However, a sector of the population was reluctant to vaccination. Therefore, this study aimed to analyze the factors associated with the acceptance of COVID-19 vaccines by citizens of northern Peru. Patients and Methods The study was observational, descriptive-corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
1
4
0
3
Order By: Relevance
“…3, September 2023: 924-931 930 the AEFI incidence of the COVID-19 vaccine at doses 1 and 2 was comparable to the trial results and in the community [27]. Other studies, on the other hand, found that because they had AEFI at dose 1, people were hesitant to receive dose 2 [9], [16], [28], [29].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…3, September 2023: 924-931 930 the AEFI incidence of the COVID-19 vaccine at doses 1 and 2 was comparable to the trial results and in the community [27]. Other studies, on the other hand, found that because they had AEFI at dose 1, people were hesitant to receive dose 2 [9], [16], [28], [29].…”
Section: Discussionsupporting
confidence: 54%
“…[15]. Previous research in Northern Peru has found a link between COVID-19 vaccine acceptance and age, family income, level of knowledge, having another chronic disease, and a more trustworthy vaccine [16]. Meanwhile, vaccination has always been a challenge in Muslim-majority countries, such as the halalness of this vaccine [17].…”
Section: Introductionmentioning
confidence: 99%
“…22,24 In the local context, no similar studies were identified that used this instrument; however, in a validation experience carried out by Yupari-Azabache et al, where knowledge, attitudes and practices were measured, a factor structure comprised of four dimensions was reported for knowledge, three dimensions for attitudes and two dimensions for practices, with optimal reliability criteria (Cronbach α between 0.81 and 0.91; McDonald ω between 0.82 and 0.92), similar to those of the present one. 25 The The approach to this zoonotic disease raises the need to incorporate a complex perspective that links knowledge of aspects such as infection mechanisms, close contact with people with the disease, topical lesions, vulnerable groups and the need for vaccination. The above shows the gap in existing knowledge and the needs of the country when considering the experience of the COVID-19 health emergency and the low levels of knowledge reported in recent studies.…”
Section: Discussionmentioning
confidence: 99%
“…The above shows the gap in existing knowledge and the needs of the country when considering the experience of the COVID-19 health emergency and the low levels of knowledge reported in recent studies. 17,27 The items related to attitudes suggest the existence of various manifestations that involve the ability to determine the impact on the reality of the country, which corresponds to a macro-systemic perspective towards a transition that involves daily life 25 and includes academic work. The above is based on the need to close gaps in knowledge by health professionals, including those in training, and thus improve communication in care processes with a preventive scope.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that a good knowledge or understanding of vaccination is important for a successful vaccination program, such as in the influenza vaccine (Yaqub et al, 2014), including in the COVID-19 vaccine (Al-kafarna et al, 2022;Yupari-Azabache et al, 2022). As this study was conducted at the beginning of the vaccination program for general adults; therefore, the experience of COVID-19 vaccination was divided into six categories, including waiting list and hesitated.…”
Section: Discussionmentioning
confidence: 99%